Determining the fracture strength and toughness of polarized GaN ceramics through the mean size of aggregates - Qin, G.S.; Guo, C.K.; Zhao, M.H.; Hu, X.; Lu, Chunsheng (2022)
The fracture strength and service life of ceramic components are closely related to their microstructures and intrinsic defects. In this paper, instead of pure data or curve fitting, the tensile strength and fracture toughness of GaN piezoelectric semi-conductive ceramics (PSCs) have been investigated based on the boundary effect model for describing the size effect of quasi-brittle materials. It is shown that the fracture toughness of polarized or depolarized GaN PSCs can be fully determined by the tensile strength and the mean size of their aggregates which follow a normal distribution. The fracture strength of polarized GaN PSCs is higher than that of depolarized ones due to the refining of aggregates. It implies that polarization can be well applied to improve the fracture resistance and durability of GaN and other PSCs.